2022
DOI: 10.1038/s41598-022-06165-z
|View full text |Cite
|
Sign up to set email alerts
|

Home-based, supervised, and mixed exercise intervention on functional capacity and quality of life of colorectal cancer patients: a meta-analysis

Abstract: This systematic review and meta-analysis of randomized controlled trials tested the effects of home-based, supervised, or mixed exercise interventions on the functional capacity (FC) and quality of life (QoL) in colorectal cancer patients. A literature search was performed using the PubMed, Embase, Cochrane, and Medline databases. Two reviewers screened the literature through March 10, 2021 for studies related to exercise and colorectal cancer. Of the 1161 screened studies in the initial search, 13 studies met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Taken together, the results of the present and earlier studies point to the possibility that PA and muscular strength can positively contribute to HRQoL among older cancer survivors by reducing symptoms and side effects and maintaining physical and mental functioning. For cancer patients and survivors who may struggle with a lack of motivation and sedentarism, a home-based intervention is advised as a more sustainable and adaptable approach [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the results of the present and earlier studies point to the possibility that PA and muscular strength can positively contribute to HRQoL among older cancer survivors by reducing symptoms and side effects and maintaining physical and mental functioning. For cancer patients and survivors who may struggle with a lack of motivation and sedentarism, a home-based intervention is advised as a more sustainable and adaptable approach [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies in childhood cancer survivors support that exercise lowers long-term risk of serious cardiac events, and there is a randomized control trial (RCT) developed specifically to investigate the impact of exercise on cardiovascular risk factors with results pending (5). Small studies have shown positive effects in the adult population of at-home exercise interventions and RCTs have shown promising outcomes of exercise effect on cancer-related fatigue and quality of life (34,35). Nonetheless, cardiac-related outcomes need to be better studied in the pediatric population (5).…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Home-based exercise programs can be a feasible strategy to improve breast cancer survivors' PA levels, quality of life, and functional performance, overcoming commonly reported barriers to PA practice, such as the lack of time, motivation, travelling, and nancial issues [13], [14]. A systematic review investigating the health outcomes of nine home-based exercise interventions in cancer survivors showed high adherence levels (71-88%) in ve of them and multiple physiological bene ts [15].…”
Section: Introductionmentioning
confidence: 99%